Refrigeration & air conditioning 101 - Ukele, Dennis P. (Pennsylvania : Page Street Publishing, 2020)
After over forty years of the refrigeration and air-conditioning industry, many changes have occurred. In order for one to keep up-to-date, most technical documents have not been seriously updated for current accuracy. This volume attempts to modernize some of the values that have undergone change over the years.
History of Refrigeration -- Basics of Thermodynamics -- Refrigeration Cycle -- Refrigeration Components -- Refrigerants -- Refrigeration Electricity and Circuitry -- Wiring Techniques -- Refrigeration Piping -- Practical Mathematics -- Brazing, Leak Check, Evacuation, Charging -- Tools -- Global Warming Potential -- Evaporators -- Condensers -- Expansion Valves -- Compressors -- Control Circuits -- Heat Load Calculation -- Workplace Safety -- Customer Satisfaction -- Record Keeping -- Service Agreements -- Air Quality and Psychrometrics -- Chillers -- Ice Machines -- Soft-Serve Ice Cream -- Duct Design -- Air Velocity -- Water Properties -- Understanding Your Instruments -- Replacement of an Expansion Valve -- Equipment Start-Up Procedures -- Compressor Diagnosis Procedures -- Evaporator Coil Repair or Replacement -- Troubleshooting -- Oil Maintenance -- Water Source Heat Pump -- Compressor Teardown --Cascade Systems -- Ammonia Refrigeration -- Supermarket Refrigeration -- Mini Splits -- Transport Refrigeration -- Dual-Heat Furnace -- Cooling Towers -- Pressure Temperature Charts -- System Refrigerant Conversion -- Start-Up Checklist -- Computer Rooms -- Dehumidifiers -- Window Unit / PTAC -- What Did You Learn? -- Answers -- Discussion of Answers -- Capacitors -- Compressor Change-Out -- Condenser Motor Replacement -- Condensing Unit Replacement -- Evacuation Procedure -- Evaporator Motor Replacement -- Advanced Services of Franklin Inc. -- Refrigerants -- Refrigerant Leaks.
Includes bibliographical references.
Keywords: REFRIGERATION AND REFRIGERATING MACHINERY